The Sundarbans, its Problems and its Possibilities - Gupta, A. C. (Indian Forester, 1957)
The large tidal delta in West Bengal known as the Sundarbans was formed ages ago in the floodplane of two large rivers, the Ganges and the Brahmaputra, emanating from the Himalayas and more or less converging in the area formerly occupied by Undivioled Bengal. In the 14th century A.D. the main flow of the Ganges having diverted to the Padma from the Bhagirathi the waterways in the western part of the Sundarbans, the whole of which now lies in West Bengal, started silting up as a result of the back rush of silt from the continental shelf in the bay into the rivers with the flow tide, and the Sundarbans thus gradually turned into a problem area. Except for a limited amount of cultivation on its borders, especially the west and the north, the entire area was wooded with mangrove species, and was an uninhabited waste until the middle of the 19th century when the British Indian Government induced the surrounding population to reclaim areas by granting many concessions. Very large areas were thus leased out to land speculators, who under the terms of the lease cleared the land of forest and put up marginal embankments to check the ingress of the tide water, which was highly saline. The lessees not however being bound to maintain the embankments in a good state of repair the tenants suffered very heavily whenever there was a breach, and breaches were not infrequent. The system not having thus proved a success it was discontinued in 1905 and no further large grants were made to land speculators. Instead, small leases were granted to cultivators and the State took upon itself the burden of putting up embankments and maintaining these. Even the State management has not been an unqualified success for breaches often occur in the embankment and large areas of cultivation are inundated with salt water. The trouble and expense of relief, rehabilitation, resealing and resweetening prove considerable. Besides, the beds of the waterways are steadily rising, particularly for the reason that the areas of normal spill have been to a great extent shut out by the erection of embankments. The result of this has been to expose the reclaimed areas to an increasing degree of risk of inundation with salt water. The remedies suggested include- ( 1 ) The resumption by State of low-lying reclaimed areas by batches, removing the embankment and leaving the areas to nature for a certain number of years so that a vertical growth of land may take place. ( 2) Reconstruction of embankments leaving a marginal strip of land between themselves and the rivers, and the afforestation of the strip. ( 3) Provision of shelter belts of suitable trees within the enclosed areas to keep out saline sprays. ( 4) The control and regulation of siltation in the rivers and the spillways. It is confidently expected that if salt in all forms can be completely kept out of the reclaimed areas the productivity of the land will greatly increase, and besides certain essential crops such as jute, which cannot be grown now, it will then be possible to cultivate.